Organizational support and pro-organizational behaviors in hotel family-SMEs: the role of emotional intelligence. Issue 4 (2nd October 2021) - Ramos, Hazel Melanie; Mustafa, Michael; Caspersz, Donella; Raveentheran, Anand
Abstract: This study explores how supportive and caring attitudes of family-SME hotels influence their non-family employees' (NFEs) pro-organizational attitudes. Specifically, the study examined whether NFEs' Perceptions of Organizational Support (POS) influenced their job satisfaction and organizational commitment and whether their emotional intelligence moderates these relationships. Empirical evidence is drawn from a sample of 172 NFEs in family-owned SME hotels in Malaysia. Findings show that POS had positive effects on NFEs' job satisfaction and organizational commitment while emotional intelligence moderated the relationship between POS and organizational commitment. The findings add new insights on how and when NFEs are satisfied with their jobs and committed to their organization.